E-COMMERCE MYSHOP BERBASIS WEBSITE PADA MONGGO DRINK THAI TEA - Avif Ego Pribadi (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2020)
Monggo Drink Thai Tea is a beverage shop located on Jl. Captain Mulyadi, Jungke Karanganyar. Food or beverage ordering system at the shop causes the problem stock Food or beverage running out when we come to shop. Therefore, it makes customers disappointed and often cancel to buy. The research objective is to build an e-commerce myshop to make it easy for consumers who make transactions through the website. This research used the waterfall method as a system development method. Data collection techniques used were interviews, observation, literature studies and questionnaires. Analysis and design involved Unified Modeling Language (UML), while testing used the webqual method. Webqual system test results show that the quality of usability has a negative effect on user satisfaction because it has a significance of 0.017> 0.05, while the quality of information has a negative effect on user satisfaction since it has a significance value of 0.706> 0.05, and the quality of service interactions has a positive effect on user satisfaction because has a significance of 0.004 <0.05. Quality of use, quality of information and quality of service interaction simultaneously affect user satisfaction since it has a significance of 0.001 <0.05.